Contradiction of The Social and Political Classes at The Beginning of Islamic Emergence - Muhammad Rikza Muqtada (LPPM UIN K.H. Abdurrahman Wahid Pekalongan, 2018)
This study analyzes the opposition of the social, political and religious classes in Arab society at the beginning of the period of Islamic presence. This study is qualitative research whose data is obtained through books, journals and other documents and is discussed with content analysis. The result of this study proved that the early Arab society in the presence of Islam valued wealth as a measure of social strata. Hierarchically, the bourgeoisie was the Arab ruler, while the proletariat and slaves became the second class of society which for many years was always under the pressure of the employer / ruler. The presence of Muhammad Saw (d. 632 AD) by calling for the establishment of social and legal justice was able to attract the proletariat and slaves to convert to Islam and jointly carry out social status resistance. The narrations of the Qur'an also support the existence of class equality between the rich and the poor, the ruler and the people, which distinguishes them only the level of faith. This kind of millenarian movement makes Islam stronger with the spirit of humanism.